Network governance of haze in Shenyang - XU JINGSI (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This paper uses the framework of network governance theory to investigate the extent to which Shenyang’s governors and the city’s citizens and businesses work together to combat the haze problem. This paper will illustrate the roles of various collaborative subjects to describe each subject’s individual and shared responsibilities in haze governance.Methodology: The researchers used a qualitative approach, gathering information from a comprehensive review of the relevant literature.Findings: The main result of this effort is a request to the government of Shenyang for their perspective on what can be accomplished through network governance in environmental governance. Network governance’s strengths lie in its ability to bring air pollution issues to the forefront of the political agenda and its potential to create and nurture sustainable development through cooperation between public and private actors at the differentiated regional levels.Implications: In this article, we apply the principles of network governance to the problem of haze weather, which in turn informs a new approach to environmental administration. Unlike top-down and bottom-up approaches, network governance encourages public participation and boos